Digital Transformation of Pesantren Blokagung Banyuwangi : The First Step in Utilizing AI to Achieve Inclusive Education in the Future - Miratu Khasanah; Indah Puspitasari; Anim Jauhariyah (ICO EDUSHA, 2024)
This study discusses digital transformation at the Darussalam Islamic Boarding School in Blokagung Banyuwangi as an effort to create an inclusive and adaptive Islamic educational environment to technological developments. This study uses a qualitative approach with a case study design, this study aims to deeply understand the digital transformation process at the Islamic boarding school. Data collection was carried out through in-depth interviews with various related parties, observations, and analysis of policy documents and Islamic boarding school digitalization programs. The data collected was analyzed using thematic analysis methods, which include coding, identifying themes, and interpreting results based on research objectives. The results of this study indicate that Islamic boarding schools are able to bridge tradition and modernity through the application of digital technology. These findings are expected to be a model for other Islamic boarding schools in Indonesia in developing technology-based Islamic education that remains rooted in Islamic values.